The transition towards sustainable diets should encourage pulse consumption in children’s diets: insights for policies in food systems - Vieira, Evla D. F. (2021)
Pulses play a central role in food system sustainability and can be the starting point toward sustainable diets. For a sustainable future, the promotion of pulses’ consumption should begin early on, during infancy. This work’s objective is to review and compile food policies that can support pulses promotion in children’s diets and provide an overview of the role of pulses in sustainable diets. A search was performed in Food and Agriculture Organization (FAO) sites and Medline database of technical reports and papers from the last 10 years (2011-2021) using the following terms: “Legume”, “pulse”, “sustainability”, “environment”, “food system”, “nutrition”, “children”, and “policies”. Subsequently, actions that could support children’s pulse consumption were selected and organized into the UNICEF´s Innocenti Framework on Food Systems for Children and Adolescents. Finally, the identified actions were discussed according to the Framework’s determinants (food supply chains, external food environments, personal food environment, and behaviors of caregivers and children). Considering the impact and feasibility of the compiled actions, reformulation of infant products with pulses and activities in school food environments seem to be priority measures because they are relatively simple to operate and have a high impact potential.